The Use of Counting Box Teaching Aids to Improve Mathematical Concept Understanding of First Grade Students at SD Negeri 1 Lemahabang - Nia Fatmawati; Sati Sati; Hema Widiawati (Journal of Educational Sciences, 2026)
This study was motivated by the low mathematical concept understanding of first-grade students at SD Negeri 1 Lemahabang. Students experienced difficulties in understanding addition concepts, identifying examples and non-examples, and solving simple mathematical problems. This study aimed to improve students’ mathematical concept understanding through the use of counting box teaching aids. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The subjects of this study were 25 first-grade students of SD Negeri 1 Lemahabang. According to Hardani et al. (2020), data collection techniques in educational research may include observation, tests, and documentation. Therefore, these techniques were used in this study. The results showed that the use of counting box teaching aids improved students’ mathematical concept understanding. In the pre-cycle stage, only 10 students (40%) achieved learning mastery. In cycle I, learning mastery increased to 16 students (64%), and in cycle II increased significantly to 23 students (92%). Therefore, the counting box teaching aid proved effective in improving students’ mathematical concept understanding in elementary school mathematics learning.